Akidah Akhlak Teacher's Methods In Improving Students' Learning Motivation After The Flash Flood Disaster At MTs Swasta Al-Ikhlas, Tanah Terban, Aceh Tamiang Regency - Burhanuddin Burhanuddin; Asnil Aidah Ritonga; Sahkholid Nasution (UMSU, 2026)
This study aims to examine the methods used by Aqidah Akhlak teachers to restore and enhance student learning motivation post-disaster at MTs Swasta Al-Ikhlas Tanah Terban. Utilizing a qualitative phenomenological approach, the study involved an Aqidah Akhlak teacher, the head of the madrasah, and seven students as subjects. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The results indicate that the teacher implemented psycho-spiritual recovery strategies through motivational reinforcement, empathetic personal approaches, and spiritual strengthening based on the values of patience, sincerity, and trust in Allah.